2012
DOI: 10.1111/j.1464-410x.2011.10682.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of urinary prostate cancer gene 3 (PCA3) scores in predicting pathological features at radical prostatectomy

Abstract: Study Type – Diagnostic (exploratory cohort) Level of Evidence 2b What's known on the subject? and What does the study add? PCA3 scores correlate to numerous histoprognostic factors, specifically tumour volume and positive surgical margins. These results may have a clinical impact in the near future on the selection of patients eligible to undergo active surveillance and nerve‐sparing surgery. OBJECTIVE To assess correlations between Prostate CAncer gene 3 (PCA3) levels and pathological features of radical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 16 publications
(28 reference statements)
3
30
1
1
Order By: Relevance
“…However, different thresholds could be appropriate in various clinical situations [8]. In contrast to Durand et al [18], no significant correlation between PCA3 score and tumour volume was found in the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…However, different thresholds could be appropriate in various clinical situations [8]. In contrast to Durand et al [18], no significant correlation between PCA3 score and tumour volume was found in the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…Other prostate cancer-specific genes, including PCA3 (prostate cancer antigen 3) (6 ), 6 TMPRSS2-ERG (transmembrane protease, serine 2) (7 ), DNA methylation (8 ), ERG (v-ets erythroblastosis virus E26 oncogene homolog) (9 ), annexin A3, and sarcosine, some of which have been proposed in combination (10,11 ), have raised enthusiasm throughout the scientific community. To date, however, the only two markers that appear clinically relevant are PCA3 and TMPRSS2-ERG (12,13 ).…”
mentioning
confidence: 99%
“…Urinary PCA3 level has been correlated with Gleason score and tumor volume in radical prostatectomy specimens, though its use in identifying high-risk disease that would otherwise be undetected is uncertain. 23, 24 Another genetic biomarker, the Prolaris ® test, is a 46-gene panel associated with tumour proliferation d 25 that is being marketed by Myriad Genetics (Salt Lake City, Utah). This 46-gene panel biomarker is designed to determine which tumors that are categorized as “low-risk” may be more aggressive and thus not appropriate for an active surveillance approach.…”
Section: Towards a Meaningful Definition Of “High-risk”mentioning
confidence: 99%